1997
DOI: 10.1111/j.1346-8138.1997.tb02794.x
|View full text |Cite
|
Sign up to set email alerts
|

OK‐432 Therapy for Recalcitrant Warts

Abstract: Twelve patients with warts recalcitrant to various treatment, including cryotherapy, were treated with OK-432 injection therapy. Six patients received only subcutaneous injection, three received only intralesional injection, and the other three received both subcutaneous and intralesional injections. Complete clearing of the warts occurred in nine (75%) of 12 patients, while the other three patients were not cured. Grouping the patients by the method of injection, the success rate of subcutaneous injection was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This drug improves the prognosis of malignant tumors, such as oral squamous cell carcinoma and uterine cervical cancer, combined with other antitumor agents 2,3 . Dermatologically, OK‐432 is also applied to recalcitrant warts, and to bowenoid papulosis and molluscum contagiosum in immunosuppressed adults 5–7 …”
Section: Discussionmentioning
confidence: 99%
“…This drug improves the prognosis of malignant tumors, such as oral squamous cell carcinoma and uterine cervical cancer, combined with other antitumor agents 2,3 . Dermatologically, OK‐432 is also applied to recalcitrant warts, and to bowenoid papulosis and molluscum contagiosum in immunosuppressed adults 5–7 …”
Section: Discussionmentioning
confidence: 99%
“…During the 1970s, local injection of OK‐432 was reported in the Japanese literature to be effective for the treatment of warts. More recently, Inui et al (51) have reported a cure rate of 75% in 12 patients, including older children with warts, by once a week intralesional or subcutaneous injections of OK‐432. OK‐432 is a penicillin‐ and heat‐treated lyophilized powder of the substrain of Streptococcus pyogenes A3.…”
Section: What's New In Immunotherapymentioning
confidence: 99%
“…The streptococcal preparation, OK-432, a penicillin-inactivated and lyphophilized preparation of the low-virulence strain, Su Streptococcus pyogenes, has been shown to have immunomodulatory and possibly therapeutic properties [13,14]. This preparation has also been found a potent inducer of IL-12 [15].…”
Section: Introductionmentioning
confidence: 99%